Розробка рецептури майонезу на основі купажованих олій для функціонального харчування - Матвєєва, Тетяна Вікторівна (Національний технічний університет "Харківський політехнічний інститут", 2015)
Функціональні продукти відіграють ключову роль у збереженні здоров'я людини. Купажовані олії, що збалансовані за жирнокислотним складом, та майонези на їх основі є прикладом продуктів функціонального призначення. Найважливішими чинниками біологічної цінності таких продуктів є кількість і співвідношення поліненасичених (ПНЖК) жирних кислот. Однак підвищення біологічної цінності олій або майонезів внаслідок збільшення ПНЖК, може супроводжуватися підвищенням швидкості їх окиснення. У статті наведено результати дослідження щодо розробки стійкого до окиснення майонезу на основі купажованої олії.

Human nutrition plays key role in maintenance of his health. One of the first plaices in human nutrition dedicated to functional nutrition, so called products of healthy nutrition. Such food have additional component that stipulates special physiological effect, which differs such products from another. Blended oils with balanced fatty acid composition on the base of domestic refined and deodorized oils are example of functional nutrition. Mayonnaises where fatty components presented by blended oils can be considered as functional nutrition too. Main factor of biological value of blended oils as well as fatty components of mayonnaises is quantity and ration between polyunsaturated (PUSFA) linoleic (w-6) and linolenic (w-3) fatty acids. According to the balanced daily diet formula needs of an adult person in oil is approximately 20 - 30 g that should contain 12 – 30 % of PUSFA. Found that among the possible methods of producing oils with a balanced composition as PUSFA ω-6 and ω-3 the most economical, compared with selection, genetic engineering, chemical or enzymatic interesterification can being oil blends . However, increase of biological value of oils and mayonnaises by increase of PUSFA quantity may be accompanied wi th raising in their oxidation ratio. The results of researches of development of mayonnaise that is stable against oxidation on the base of balanced blended oil presented in the article.
Development of mayonnaise formulations for functional nutrition based on blended oils
Keywords: поліненасичені жирні кислоти; мононенасичені жирні кислоти; окиснення; майонези; купажі; blends of polyunsaturated fatty acids; mayonnaise; monounsaturated fatty acids; oxidation